Inverse transition in the dipolar frustrated Ising ferromagnet : the role of domain walls - Araújo Velasque, Luciana (2014)
Fil: Araújo Velasque, Luciana. Universidade Federal do Rio Grande do Sul. Instituto de Física. Departamento de Física; Brasil.